Unveiling Gender Disparities in ADHD: A Literature Review on Factors and Impacts of Late Diagnosis in Females (2010-2023) - Kayla, Almekhlafi; Sonia, Jain (Journal of Women's Mental Health, 2024)
This exploratory study investigates factors and consequences of underdiagnoses or late diagnoses of attention deficit hyperactivity disorder (ADHD) in females favoring males in the referral, diagnosis, and treatment processes resulting in  gender disparities. A literature review in PubMed, PsychINFO, PsychArticles, and PsychiatryOnline from 2010 to 2023 underscores significant implications of delayed ADHD diagnosis in females, hindering timely access, support, and interventions during critical developmental years. Factors associated with underdiagnosis of ADHD among girls include gender differences in symptomology presentation, comorbidity, and gender bias among parents, teachers, and healthcare providers. We highlight the role of ethnicity and cultural factors. This bias prevents girls from receiving necessary ADHD support and treatment, impacting their health, social, and economic outcomes into adulthood. We summarize strategies to urgently address gaps in ADHD research and practice. Raising awareness among communities, healthcare providers, educators, and parents is vital to alleviate these gender disparities. By illuminating factors contributing to delayed diagnoses, the study informs policymakers and stakeholders, facilitating targeted interventions to improve early detection and treatment outcomes for females with ADHD.
Keywords: Attention Deficit Hyperactivity Disorder; ADHD; ADHD Comorbidity; Postpartum ADHD; Mental Health; Maternal ADHD; Gender bias; Gender Disparities